2022
DOI: 10.3390/min12010077
|View full text |Cite
|
Sign up to set email alerts
|

Handheld LIBS for Li Exploration: An Example from the Carolina Tin-Spodumene Belt, USA

Abstract: Laser-induced breakdown spectroscopy (LIBS), which has recently emerged as tool for geochemical analysis outside the traditional laboratory setting, is an ideal tool for Li exploration because it is the only technique that can measure Li in minerals, rocks, soils, and brines in-situ in the field. In addition to being used in many products essential to modern life, Li is a necessary element for a reduced carbon future and Li–Cs–Ta (LCT) granitic pegmatites are an important source of Li. Such pegmatites can have… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(21 citation statements)
references
References 98 publications
0
21
0
Order By: Relevance
“…LIBS is a versatile method that can be performed in the laboratory or in‐situ with a portable device and can provide qualitative and quantitative analyses of most elements on the periodic table. It is an ideal technique to measure light elements such as Li during fieldwork (Fabre et al, 2022; Harmon et al, 2005; Wise et al, 2022).…”
Section: Methodsmentioning
confidence: 99%
“…LIBS is a versatile method that can be performed in the laboratory or in‐situ with a portable device and can provide qualitative and quantitative analyses of most elements on the periodic table. It is an ideal technique to measure light elements such as Li during fieldwork (Fabre et al, 2022; Harmon et al, 2005; Wise et al, 2022).…”
Section: Methodsmentioning
confidence: 99%
“…94,95 Once the location of the mining site has been determined from the laboratory analysis, portable LIBS instruments can be used directly on site to guide the mining expansion. 96,97 Even though the sensitivity and resolution of such handled instruments are limited, they provide fast results that can strongly affect mining extraction efficiency. Indeed, lithium is not the only critical, strategic, or precious element.…”
Section: ■ Insights Into Libs Imagingmentioning
confidence: 99%
“…LCT pegmatites (containing Li-Cs-Ta) are an important source of Li. Such pegmatites can have varying degrees of enrichment in Li, Rb, Cs, Be, Sn, Ga, Ta>Nb, B, P, and F. The crustal abundance of Li is 17 µg/g, but the concentration in the mineralized rocks can go up to ~ 3% (Wise et al 2022). Hyperspectral imaging data (HSI) generated by portable VNIR, and SWIR spectrometer was also utilized for Li exploration studies.…”
Section: Plibs In Li-exploration Studiesmentioning
confidence: 99%
“…Figure 11 presents the LIBS spectra of three Li-rich minerals obtained from different Li-rich minerals in the entire wavelength range (Pochon et al 2021). Wise et al (2022) recently demonstrated the potential of pLIBS in the LCT pegmatites of the Carolina Tin-Spodumene Belt (CTSB) situated in the Kings Mountain Shear Zone, USA. pLIBS was utilized for the identification and quantification of lithium (detection limit < 100 µg/g), measurement of K/Rb ratios, lithium mapping, and depth profiling.…”
Section: Plibs In Li-exploration Studiesmentioning
confidence: 99%